Sequential transmission electron microscopy observation of the shape change of gold nanorods under pulsed laser light irradiation. (31st March 2019) - Aso, Kohei; Shigematsu, Koji; Yamamoto, Tomokazu; Matsumura, Syo
Abstract : In situ high-resolution observations were performed on gold nanorods under near-infra-red pulsed laser irradiation. Their shapes changed from rod to barrel, while the original single-crystalline structure was maintained. The temporal changes of their surface area and volume indicate the heterogeneous deformation of nanorods under laser illumination. Abstract: In situ sequential high-resolution observations were performed on gold nanorods under near-infra-red pulsed laser irradiation using a high-voltage electron microscope attached to a pulsed laser illumination system. The original nanorods were single crystals; the longer axes were oriented along [001]. Under laser light irradiation with λ = 1064 nm with an average intensity per pulse of 980 or 490 J/m 2, the shape of the nanorods changed from rod to barrel surrounded by the {111} and {001} facets, while the original single-crystalline structure was maintained. The side surfaces with <110> direction were reconstructed into zig–zag fine structures consisting of narrow {111} facets. The temporal evolution of the volume and surface area during irradiation was evaluated based on the images, assuming that the particles have a rotational symmetry along their longer axes. The surface area was stepwise decreased during the shape change using pulse shots of 980 J/m 2 while the volume was maintained. On the other hand, several repeated shots were required to induce the shape change when the averaged intensity was reduced to 490 J/m 2 per pulse. In addition to the surface area, the volume was reduced under the latter condition during the shape change due to the evaporation of atoms. The quantitative analysis of the temporal changes indicates the heterogeneity of the atomic excitation or heating of gold nanorods induced by pulsed laser illumination.